In-situ growing protective Cr-substituted goethite film on iron shavings (Fe0) as efficient catalytic ozonation catalysts: A comparative study. (15th March 2021) - Lin, Xiaozi; Li, Xufang; Fei, Jiaoran; Ma, Luming; Huang, Yuanxing
Abstract: H2 O2 -modified iron shavings (HMI) with surface γ-FeOOH film were effective as a catalyst in catalytic ozonation, but the iron leaching and loss of surface component limited its application. In this study, Cr-modified iron shavings (CrMI) was developed by introducing Cr 3+ to promote Cr-substituted goethite (α-Fe(Cr 3+ )OOH) film formation on iron shavings. The variety in stability and catalytic performance between CrMI and HMI were compared. The α-Fe(Cr 3+ )OOH film was compact while the γ-FeOOH film contained abundant voids and microcracks as observed from SEM. After long-time ozonation, α-Fe(Cr 3+ )OOH film was thin and homogeneous whereas γ-FeOOH film grew thicker through inner iron layer corrosion as indicated by XPS etching. The α-Fe(Cr 3+ )OOH film has 63% reduction in corrosion current densities (22.95 μA) and 96% reduction of donor densities (3.40 × 10 20  cm −3 ) as well as 9 times increase in polarization resistance (4399.0 Ω cm 2 ), which verified that it was more stable and less defective. Owing to the protective properties of α-Fe(Cr 3+ )OOH film, iron leaching of CrMI were reduced for 85% with only 4.1 mg L −1 of total iron concentration detected in solution, and surface loss of CrMI were reduced for 91% with only 5.8 NTU of turbidity left in the solution after catalytic ozonation. Moreover, the addition of CrMI as catalyst in ozonation led to slightly higher mineralization rate of 79% for organic pollutants as the results of higher surface acid sites density and more hydroxyl radicals generation. It also presented excellent reusability based on 20 h successive run with unnoticeable performance decay and metal release. These results revealed that, with excellent stability and high catalytic performance, CrMI was highly competitive for long-term application in wastewater treatment. Graphical abstract: Image 1 Highlights: CrMI was developed by introducing Cr 3+ to promote compact α-Fe(Cr 3+ )OOH film formation on iron shavings. The stability and catalytic performance of CrMI were compared to HMI with γ-FeOOH film grown on iron shavings. α-Fe(Cr 3+ )OOH film was more protective and anti-corrosive investigated by electrochemical measurements. Lower iron leaching and less surface department with higher catalytic performance were observed in CrMI catalytic process. Surface acid sites density andOH generation in CrMI system were more abundant.